Use of Nickel Slag Waste as Coarse Aggregate in Concrete - Andi Ahdan Amir; Sukman Sukman; Mahmud Mahmud; Hasrudin Hasrudin (Faculty of Engineering, Andi Djemma University, 2022)
Indonesia is the largest nickel producer in the world. but from another aspect, the problem of ex-mining pits, combustion ash waste, nickel slag and others are environmental issues in the nickel mining industry (nikel.co.id, 2020). Currently, the Ministry of Industry through the research and development unit is trying to raise the potential of nickel slag or slag so that it can be used as industrial raw material that is in line with environmental management in the context of a sustainable economic program (antaranews.com, 2020). Based of this study was conducted on the use of nickel slag as a substitute for coarse aggregate in concrete. This research is an experimental study with the objectives of analyzing the physical and mechanical characteristics of nickel slag, analyzing the compressive strength of concrete using nickel slag as a substitute for coarse aggregate, and analyzing the optimal percentage of nickel slag used as a substitute for coarse aggregate. The results of this study indicate that the use of nickel slag as a substitute for coarse aggregate for 20 MPa concrete, and unable to achieve the planned average compressive strength of 20 MPa plus a margin of 12 MPa, resulted in a decrease in compressive strength and did not provide quality improvement. concrete. The application of nickel slag as a substitute for coarse aggregate in structural concrete with a design compressive strength â‰¥ 20 MPa is not recommended.